2006
DOI: 10.1111/j.0021-9029.2006.00095.x
|View full text |Cite
|
Sign up to set email alerts
|

Three Years Later: A Follow‐Up Study of Parents' Assessments of Their Children's Competencies1

Abstract: The present study is a follow‐up of one that was designed to examine the changes that have occurred in parents' views of a child's competencies during the child's first 3 years of school. Parents with a university education (N=180) and a vocational education (N=249) were asked to assess their children's competencies in domains representing school subjects and abilities in preschool and at the end of the 1st and 3rd school years. The findings indicated that parents' initial optimistic views had prevailed. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 28 publications
0
22
2
Order By: Relevance
“…Another important factor to consider is pupils' social background, as measured by their parents' occupation, educational level, or social class. There is research evidence to show that these social-positional factors are highly relevant for studies of the social representations of intelligence (Räty et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Another important factor to consider is pupils' social background, as measured by their parents' occupation, educational level, or social class. There is research evidence to show that these social-positional factors are highly relevant for studies of the social representations of intelligence (Räty et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Culturally our sample was very homogenous. (More highly detailed information of the longitudinal research and the representativeness of the sample is reported in Räty, Kasanen, & Honkalampi, 2006).…”
Section: Participantsmentioning
confidence: 99%
“…Highly educated parents are generally closer to the school and its definition of ability as essentially a cognitive-verbal feature than other parents (Räty and Snellman 1998), and they tend to attribute more cognitive-verbal skills to their child than others do (e.g., Räty et al 2006a). Moreover, in our earlier study, we found that the self-serving attribution pattern was stronger among academically than vocationally educated parents (Räty et al 2006b; see also Kärkkäinen et al 2009).…”
mentioning
confidence: 46%
“…Interestingly, no relative gender-difference in the teachers' and parents' perceptions of girls' and boys' improvement potential existed in mathematics. It is possible that the parents and teachers are not concerned about the girls' mathematical skills since, even if boys are usually seen to be better in mathematics, girls are generally seen to perform better at other school subjects (e.g., Räty et al 2006a). …”
Section: Discussionmentioning
confidence: 99%